Pengaruh Moralitas Individu dan Internal Control terhadap Pencegahan Kecurangan dalam Pengelolaan Dana Desa - Achawati, Sitti; Usman , Usman; Taruh, Victorson (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The purpose of this study was to determine individual morality and internal control on fraud prevention in village fund Management in Kabila Bone District, Bone Bolango Regency. The research methodology used in this research is quantitative method with data collection techniques using questionnaire surveys and observations. The number of respondents in this study were 63 respondents consisting of the Village Head, Village Secretary, Village Treasurer, Head of General Affairs and Planning, Head of Welfare and Services, Head of Hamlet and Chairman of the Village Consultative Body throughout Kabila Bone District. The tools used in this study used multiple linear regression analysis. Based on the results of this study, it is known that individual morality has a significant effect on preventing fraud in the management of village funds in Kabila Bone District and internal control has a significant positive effect on preventing fraud in the management of village funds in Kabila Bone District.